Potensi Fitolarvasida Ekstrak Daun Sirsak dan Umbi Bawang Putih terhadap Larva Aedes aegypti - Wahyu Denny Setioko; Listiana Masyita Dewi (WMJ (Warmadewa Medical Journal), 2026)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the bite of Aedes sp. mosquitoes carrying the dengue virus. One of the current efforts to control DHF is through abatement using temephos. However, long-term use of temephos can lead to the development of insecticide resistance, thereby reducing its effectiveness. As an alternative, efforts are needed to develop larvicides derived from natural plant-based ingredients, such as soursop leaves and garlic bulbs. This study aimed to compare the effectiveness of ethanol extracts of soursop leaves and garlic bulbs on the mortality of Aedes aegypti larvae. This study was a true experimental study with a post-test only control group design. The experiment was conducted in three replications using 25 Aedes aegypti instar III–IV larvae in 12 groups, consisting of one positive control group, one negative control group, and five treatment groups for each extract at concentrations of 0.05%, 0.1%, 0.2%, 0.4%, and 0.8%. Based on the Post Hoc Mann-Whitney statistical analysis, each tested extract showed the highest larvicidal effect at a concentration of 0.8%, with comparisons to the positive control showing a p-value > 0.05. The LC50 values of the soursop leaf and garlic bulb extracts were 0.102 and 0.116, respectively. Thus, it can be concluded that ethanol extracts of soursop leaves and garlic bulbs are effective as phytolarvicidal agents against Aedes aegypti larvae; however, the ethanol extract of soursop leaves had a stronger effect than that of garlic bulbs.